Good Corporate bagi Efektivitas Sistem Moral Perbankan Syariah - Syafruddin Arif (Universitas Islam Indonesia, 2011)
The good corporate governance (GCG) for islamic banks nowadays is necessary in the entire world. That's due to significance of the stakeholders trust towards islamic banks its self GCG as codes of moralis not in the contrary with islamic principles. But in practice, the GCG could serve as an obligatory and formal instrument for delivering transparant public financial reports of the islamic banks. In its initial growth, serious research work over recent decades has shown that Islamic banking is not only feasible and viable, it is an efficient and productive way of financial intermediation. But the efficiency of the islamic banking enconter much barriers, though it applied the GCG for several constraints, such as corruption culture, double-book keeping, and power approach.